Evaluation of customer relationship system efficiency: Applying of total cost of ownership approach - Jasilionienė, Regina; Tamošiūnienė, Rima (Journal of Business Economics and Management, 2009)
Calculating total cost of ownership (TCO) and benefits, building a business case and applying financial measurement methodologies help a company make right customer relationship system for investments solution and build compelling justification for its customer relationship system project. In addition, ongoing measurement of customer relationship system (CRS ) benefits ensures that an enterprise receives expected advantages and achieves strategic objectives. In this paper peculiarities of TCO economic efficiency are analysed. Evaluation method application when developing, using and expanding CRS is being considered, strengths and weaknesses of cost‐oriented approach are discussed. Authors present and interpret their empirical research results.First Publish Online: 14 Oct 2010